The effect of bacteria, enzymes and inulin on fermentation and aerobic stability of corn silage - S Peymanfar (Iranian Journal of Microbiology, 2012)
Background and Objectives: Ensiling is a conservation method for forage crops. It is based on the fact that anaerobe lactic acid bacteria (LAB) convert water-soluble carbohydrates into organic acids. Therefore, pH decreases and the forage is preserved. The aim of this study was to isolate special kinds of lactic acid bacteria from silage and to study the effect of bacteria, inulin and enzymes as silage additives on the fermentation and aerobic stability of the silage. Materials and Methods: The heterofermentative LAB were isolated from corn silages in Broujerd, Iran and biochemically characterized. Acid tolerance was studied by exposure to acidic PBS and growth in bile salt was measured by the spectrophotometric method. Results: The results of molecular analysis using 16SrDNA sequences showed that the isolates belonged to Lactobacillus and Enterococcus genera. To enhance stability in acidic environment and against bile salts, microencapsulation with Alginate and Chitosan was used. The Lactobacillus plantarum strains were used as control. The inoculants (1 × 107 cfu/g) alone or in combination with inulin or in combination with enzymes were added to chopped forages and ensiled in 1.5-L anaerobic jars. Conclusion: Combination of the isolates Lactobacillus and Enterococcus with inulin and enzymes can improve the aerobic stability of corn silage.